2017
DOI: 10.1002/jsfa.8243
|View full text |Cite
|
Sign up to set email alerts
|

Application and bioactive properties of CaTI, a trypsin inhibitor from Capsicum annuum seeds: membrane permeabilization, oxidative stress and intracellular target in phytopathogenic fungi cells

Abstract: This paper shows the antifungal activity of protease inhibitors such as CaTI against phytopathogenic fungi. Antimicrobial peptides, among which the trypsin protease inhibitor family stands out, are present in different species of the genus Capsicum and are part of the chemical arsenal that plants use to defend themselves against pathogens. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 54 publications
(96 reference statements)
4
15
0
Order By: Relevance
“…Santos et al [13] isolated the Fa5 fraction of C. annuum fruits, which showed high antimicrobial activity only against species of the genus Fusarium. In contrast, Silva et al [28] showed that CaTI, a proteinase inhibitor isolated from C. annuum seeds, was able to inhibit only the growth of fungi of the genus Colletotrichum. Slazak et al [32] isolated several cytotoxins from Viola odorata, namely, cyO2, cyO3, cyO13 and cyO19, and showed that all these showed inhibitory activity against all fungi tested (F. oxysporum, F. graminearum, F. culmorum, Mycosphaerella fragariae, and Botrytis cinerea).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Santos et al [13] isolated the Fa5 fraction of C. annuum fruits, which showed high antimicrobial activity only against species of the genus Fusarium. In contrast, Silva et al [28] showed that CaTI, a proteinase inhibitor isolated from C. annuum seeds, was able to inhibit only the growth of fungi of the genus Colletotrichum. Slazak et al [32] isolated several cytotoxins from Viola odorata, namely, cyO2, cyO3, cyO13 and cyO19, and showed that all these showed inhibitory activity against all fungi tested (F. oxysporum, F. graminearum, F. culmorum, Mycosphaerella fragariae, and Botrytis cinerea).…”
Section: Discussionmentioning
confidence: 92%
“…This fraction was separated by C18 reversed-phase column ( Figure 1B) and the ten fractions obtained (Figure 2), presented antifungal activity against four different species of phytopathogenic fungi (Figure 3). In recent years, our group has reported several plant AMPs as potent growth inhibitors of microorganisms [27][28][29]. Games et al [27] purified a defensin from Phaseolus vulgaris seeds, called PvD1, which showed inhibitory activity against yeasts and phytopathogenic fungi at concentration of 100 μg.ml −1 .…”
Section: Discussionmentioning
confidence: 99%
“…This protein had the ability to permeabilize the plasma membrane of Saccharomyces cerevisia e and Candida albicans cells after 24 h of growth. Silva et al [7] reported growth inhibition of the fungi C. gloeosporioides and C. lindemuthianum by the CaTI inhibitor, in addition to showing the ability of the protein to permeabilize the membrane of all the tested fungi, what indicates the importance of protease inhibitors in the defense of plants against several pathogens. The protease inhibitors are constitutively present in all plant kingdoms, being mainly located in the reserve tissues, in addition to being produced in response to injuries caused by insects or even by fungi and bacteria [41–43].…”
Section: Resultsmentioning
confidence: 99%
“…These AMPs can be expressed in high concentrations upon the aggression of some pathogen or upon exposure to biotic or abiotic stresses. Effectively, antimicrobial peptides tend to act directly in the region of injury against the aggressor and can be found in several plant organs, such as seeds, reproductive organs, tubers, fruits and flowers, and in almost all plant species [7].…”
Section: Introductionmentioning
confidence: 99%
“…against various filamentous fungi and found that all eight fractions were able to inhibit the growth of Fusarium lateritium, Fusarium solani and Fusarium oxysporum but were not able to inhibit the growth of C. gloeosporioides . Silva et al [21] tested CaTI , a protease inhibitor obtained from C. annuum seeds, on the growth of fungi Colletotrichum lindemuthianum, C. gloeosporioides, F. solani and F. oxysporum and found inhibition against fungi of the genus Colletotrichum , but not for those of the genus Fusarium . In microscopic analysis, it was concluded that CaTI reduced the growth of the mycelium of C. gloeosporioides .…”
Section: Discussionmentioning
confidence: 99%